A novel composite type I collagen scaffold with micropatterned porosity regulates the entrance of phagocytes in a severe model of spinal cord injury. Issue 5 (9th March 2016) - Snider, Silvia; Cavalli, Andrea; Colombo, Francesca; Gallotti, Alberto Luigi; Quattrini, Angelo; Salvatore, Luca; Madaghiele, Marta; Terreni, Maria Rosa; Sannino, Alessandro; Mortini, Pietro
Abstract: Traumatic spinal cord injury (SCI) is a damage to the spinal cord that results in loss or impaired motor and/or sensory function. SCI is a sudden and unexpected event characterized by high morbidity and mortality rate during both acute and chronic stages, and it can be devastating in human, social and economical terms. Despite significant progresses in the clinical management of SCI, there remain no effective treatments to improve neurological outcomes. Among experimental strategies, bioengineered scaffolds have the potential to support and guide injured axons contributing to neural repair. The major aim of this study was to investigate a novel composite type I collagen scaffold with micropatterned porosity in a rodent model of severe spinal cord injury. After segment resection of the thoracic spinal cord we implanted the scaffold in female Sprague‐Dawley rats. Controls were injured without receiving implantation. Behavioral analysis of the locomotor performance was monitored up to 55 days postinjury. Two months after injury histopathological analysis were performed to evaluate the extent of scar and demyelination, the presence of connective tissue and axonal regrowth through the scaffold and to evaluate inflammatory cell infiltration at the injured site. We provided evidence that the new collagen scaffold was well integrated with the host tissue, slightly ameliorated locomotor function, and limited the robust recruitment of the inflammatory cells at the injury site during both the acute and chronic stage in spinal cord injured rats. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1040–1053, 2017.